The News of the World and the British Press, 1843-2011
XIII, 311 p.
Keywords: This volume is the first scholarly treatment of the News of the World from news-rich broadsheet to sensational tabloid. Contributors uncover new facts and discuss a range of topics including Sunday journalism, gender, crime, empire, political cartoons, the mass market, investigative techniques and the Leveson Inquiry.